The Application of Vacuum-Assisted Closure Device in the Management of Empyema Necessitans - Yasser Aljehani; Zahra Al-Matar; Samah Nawar (Case Reports in Surgery)
Vacuum-assisted closure (VAC) is gaining popularity in the management of many types of acute and chronic wounds. The use of VAC devices in thoracic surgery is limited, but it appears to be promising in complex cases of empyema thoraces. We report a case of empyema necessitans, in which VAC was used to achieve complete wound healing after open drainage which was communicating with the pleural space.